Avaliaç\~ao dos fundos setoriais: CT-Info - Luis Claudio Kubota; Mauro Oddo Nogueira; Daniela Nogueira Milani (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This articles adopts a differentiated methodology for evaluating sectoral funds, and its aim is to analyze the functioning and the impacts of CT-Info in what regards to its focus: to support projects in Brazilian information technology firms. To accomplish this goal, the research tried to answer three fundamental questions: what is the profile of the firms supported by CT-Info? How was the dynamics of utilization of the resources? What was the motivation for firms to use or not to use the instrument? In one hand, results point to a capture of the instrument by the Academy. On the other hand, for the few supported firms, despite bureaucratic difficulties, the obtained results were very important.
Keywords: O39; 330; sectorial funds; information technology; national innovation system